2010
DOI: 10.5194/angeo-28-1133-2010
|View full text |Cite
|
Sign up to set email alerts
|

Satellite traces, range spread-F occurrence, and gravity wave propagation at the southern anomaly crest

Abstract: Abstract. Range spread-F (RSF) and occurrence of "satellite" traces prior to RSF onset were studied at the southern peak of the ionospheric equatorial anomaly (EA). Ionograms recorded in September 2007 at the new ionospheric station of Tucumán, Argentina (26.9 • S, 294.6 • E, dip latitude 15.5 • S), by the Advanced Ionospheric Sounder (AIS) developed at the Istituto Nazionale di Geofisica e Vulcanologia (INGV), were considered.Satellite traces (STs) are confirmed to be a necessary precursor to the appearance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 40 publications
2
31
0
Order By: Relevance
“…The spread-F occurrences are continuously investigated in various regions to ascertain the hypothesis of ESF characteristics and occurrences. For instance, the issues in the equatorial ionosphere-thermosphere electrodynamics over American and Southeast Asia sectors (Abdu, 2001;Cabrera et al, 2010;Candido et al, 2011;Maruyama et al, 2007) or the investigations to find out the relation between the spread-F occurrence and the sporadic-E (Es) characteristics over the Brazilian conjugate point equatorial experiment (COPEX) (Batista et al, 2008). The statistics of spread-F occurrence over different regions confirm that at the different geomagnetic declinations, latitudinal and longitudinal regions, ESF occurrence and intensity have distinct annual or seasonal patterns (Abdu et al, 1981;Maruyama and Matuura, 1984;Sastri, 1999;Maruyama et al, 2002Maruyama et al, , 2007Saito and Maruyama, 2007;Wang et al, 2008Wang et al, , 2010Hoang et al, 2010;Amabayo et al, 2011;Pezzopane et al, 2013).…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…The spread-F occurrences are continuously investigated in various regions to ascertain the hypothesis of ESF characteristics and occurrences. For instance, the issues in the equatorial ionosphere-thermosphere electrodynamics over American and Southeast Asia sectors (Abdu, 2001;Cabrera et al, 2010;Candido et al, 2011;Maruyama et al, 2007) or the investigations to find out the relation between the spread-F occurrence and the sporadic-E (Es) characteristics over the Brazilian conjugate point equatorial experiment (COPEX) (Batista et al, 2008). The statistics of spread-F occurrence over different regions confirm that at the different geomagnetic declinations, latitudinal and longitudinal regions, ESF occurrence and intensity have distinct annual or seasonal patterns (Abdu et al, 1981;Maruyama and Matuura, 1984;Sastri, 1999;Maruyama et al, 2002Maruyama et al, , 2007Saito and Maruyama, 2007;Wang et al, 2008Wang et al, , 2010Hoang et al, 2010;Amabayo et al, 2011;Pezzopane et al, 2013).…”
Section: Introductionmentioning
confidence: 70%
“…In addition, Pezzopane et al (2013) found that satellite traces (STs), caused by gravity waves (GWs) propagation, are precursor to the RSF appearance at Chiangmai, and also at TUC, Argentina, and TNJ, Indonesia, which are located in the southern hemisphere. Also, Cabrera et al (2010), by using ionograms recorded at Tucuman, Argentina, in September 2007, previously found that STs are precursor to the RSF appearance. Furthermore, Saito and Maruyama (2006) verified that the meridional neutral wind is another important factor that controls the plasma bubble generation at the magnetic conjugate stations of CMU and KTB.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon was first reported by Booker and Wells (1938) while investigating the ionograms recorded at Huancayo, Peru. The equatorial spread-F (ESF) usually occurs just after local sunset and the scale sizes of the Published by Copernicus Publications on behalf of the European Geosciences Union.…”
Section: Introductionmentioning
confidence: 93%
“…The exact explanation of mechanisms leading to different occurrence rates and their relative roles requires sophisticated numerical simulations, which is outside the scope of this experimental study. GW seeding as a potential mechanism for the initiation of ESF and plasma bubble development has been discussed in many experimental and theoretical papers (e.g., Abdu et al 2009b;Cabrera et al 2010;Hysell et al 2014, and references therein). Unfortunately, our observations are under the crest of the EIA rather than at the geomagnetic equator, where the initiation is expected, and the GW seeding in the bottomside ionosphere should be important.…”
Section: Comparison With Other Measurements and Relation To Neutral Wmentioning
confidence: 99%
“…It is generally accepted that equatorial spread F (ESF) and plasma bubbles result from Rayleigh-Taylor instability triggered during the uplift of the F layer owing to the prereversal enhancement of the eastward (zonal) electric field and development of the steep plasma density gradient as the bottomside ionosphere becomes depleted after sunset (Fejer et al 1999;Stolle et al 2006;Abdu et al 2009a;Kelley 2009). The day-to-day variability and the Open Access *Correspondence: jachu@ufa.cas.cz 1 Institute of Atmospheric Physics, Bocni II/1401, 14131 Prague 4, Czech Republic Full list of author information is available at the end of the article roles of all factors that contribute to plasma bubble formation and spread F observation such as gravity wave (GW) seeding, neutral winds, angle between magnetic meridian, and solar terminator, however, remain enigmatic and are subjects of intense investigation (Kudeki et al 2007;Abdu et al 2009a, b;Cabrera et al 2010;Hysell et al 2014). The prereversal enhancement of the eastward electric field and hence the enhancement of the plasma vertical drift vary with longitude and season and are likely an important controlling factor for large-amplitude equatorial plasma bubble development (Huang and Hairston 2015).…”
Section: Introductionmentioning
confidence: 99%